“Para que se ejerzan en ellos las disposiciones legales y por descargo de conciencia”: escrituras de reconocimiento en Cuenca (Ecuador), 1865-1875 (Debates) - Arteaga Auquilla, María Teresa (2023)
The subject of this article is child recognition in Cuenca during the second half of the 19th century. Such acknowledgment entails a two-way process involving the acknowledgers (fathers) and the acknowledged (sons and daughters) in two clearly differentiated contexts: the family and society, with specific moral and economic implications. This study analyzes acknowledgment documents and wills executed in the city.